2012
DOI: 10.3183/npprj-2012-27-01-p104-111
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fibre properties, fines content and surfactant addition on dewatering, wet and dry web properties

Abstract: Speed of paper machines is often limited by the drainage rate of the furnish and the mechanical properties of the wet web, i.e. the tension and relaxation properties. In this study, the effects of alteration of fibre properties and fines content by gentle and harsh refining on dewatering as well as on wet and dry web properties were determined. Both types of refining or addition of fines prolonged the dewatering time but also improved the mechanical properties. Harsh refining with much fibre cutting resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The fibrous network of BC and NFC possesses high tensile strength of 9.7 kN m -1 and 6.6 kN m -1 , respectively [31]. A paper made of pulp fibres, on the other hand, possesses a tensile strength from 1.5-5 kN m -1 [32,33]. This translates to higher measured tensile strengths for the nonwoven preforms with NFC and BC binders compared to the pulp binder.…”
Section: Resultsmentioning
confidence: 99%
“…The fibrous network of BC and NFC possesses high tensile strength of 9.7 kN m -1 and 6.6 kN m -1 , respectively [31]. A paper made of pulp fibres, on the other hand, possesses a tensile strength from 1.5-5 kN m -1 [32,33]. This translates to higher measured tensile strengths for the nonwoven preforms with NFC and BC binders compared to the pulp binder.…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants can have either negative or positive effects on paper strength (Touchette and Jenness 1960;Lindqvist et al 2009). Negative effects, when observed, can be attributed partly to a tendency of surfactants to accumulate at phase boundariessome of which are likely to be the potential bonding sites between fibers during the formation of paper.…”
Section: Contaminationmentioning
confidence: 99%
“…They tried to achieve a constant fines content by producing and discarding 10 handsheets before sheets for mechanical testing were formed. In the study conducted by Lindqvist et al (2012), the method chosen was the one suggested by the Scandinavian Pulp, Paper and Board Committee (SCAN-CM 64:00 (2000)), which also uses a white water recirculation system and links the amount of fines retained in the handsheets with the dewatering time. In this case, the dewatering time must remain constant even when preparing additional sheets.…”
Section: Introductionmentioning
confidence: 99%
“…They observed changes in the sheet's density and optical properties and a higher anionic charge in the fines fraction compared to that of the long fiber fraction. The addition of secondary fines to the pulp was also shown to negatively affect the dewatering behavior, prolonging dewatering (Lindqvist et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation